Interaction Between Stress and Addiction: Contributions From Latin-American Neuroscience - Torres-Berrio, Angélica; Cuesta, Santiago; Lopez-Guzman, Silvia; Nava-Mesa, Mauricio O. (Frontiers in Psychology, 2018)
Drug addiction is a chronic neuropsychiatric disorder that escalates from an initial exposure to drugs of abuse, such as cocaine, cannabis, or heroin, to compulsive drug-seeking and intake, reduced ability to inhibit craving-induced behaviours, and repeated cycles of abstinence and relapse. It is well-known that chronic changes in the brain’s reward system play an important role in the neurobiology of addiction. Notably, environmental factors such as acute or chronic stress affect this system, and increase the risk for drug consumption and relapse. Indeed, the HPA axis, the autonomic nervous system, and the extended amygdala, among other brain stress systems, interact with the brain's reward circuit involved in addictive behaviors. There has been a growing interest in studying the molecular, cellular, and behavioral mechanisms of stress and addiction in Latin-America over the last decade. Nonetheless, these contributions may not be as strongly acknowledged by the broad scientific audience as studies coming from developed countries. In this review, we compile for the first time a series of studies conducted by Latin American-based neuroscientists, who have devoted their careers to studying the interaction between stress and addiction, from a neurobiological and clinical perspective. Specific contributions about this interaction include the study of CRF receptors in the lateral septum, investigations on the neural mechanisms of cross-sensitization for psychostimulants and ethanol, the identification of the Wnt/β-catenin pathway as a critical neural substrate for stress and addiction, and the emergence of the cannabinoid system as a promising therapeutic target. We highlight animal and human studies, including for instance, reports coming from Latin American laboratories on single nucleotide polymorphisms in stress-related genes and potential biomarkers of vulnerability to addiction, that aim to bridge the knowledge from basic science to clinical research.